THE ANALYSIS OF MANDIBULAR TRABECULAE ALVEOLAR PROCESS ON POST-MENOPAUSAL WOMEN THROUGH PANORAMIC RADIOGRAPH: ANALISIS TRABEKULA PROSESUS ALVEOLAR MANDIBULA PADA WANITA PASCA MENOPAUSE MENGGUNAKAN RADIOGRAF PANORAMIK - azhari, azhari (Dentika: Dental Journal, 2017)
The alveolar process is the most supporting tooth containing trabeculae and has the highest metabolic rate in the mandibular body of post-menopausal women. The decreasing in estrogens level on post-menopausal women results a faster reaction than men for 2-3 times. This research aims to determine the bone quality based on trabeculae alveolar process analysis using panoramic radiographs. The research methodology was to conduct 67 samples of panoramic radiographs from RSGM Unpad. This research applied observational analytic methodology by taking cross-sectional data using secondary data on three groups of bone quality based on measurement using DEXA t-score (normal, osteopenia and osteoporosis). The panoramic radiograph data processing was conducted with Image J software by separating the background and foreground (trabeculae). A focus of 30x30 mm ROI in the alveolar distal portion of the left and right mandibular second premolar teeth, and calculation of trabecular area. Result: average of normal trabecular area: 82.35%, osteopenia: 73.9% and osteoporosis: 68.7% respectively. The difference between normal and osteoporosis was discovered, but no difference was found between normal and osteopenia with p <0.05. This research concludes that the region of interest trabecular of alveolar process with panoramic radiograph can be used to detect osteoporosis on post-menopausal women.